2008
DOI: 10.1073/pnas.0805325105
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor ligands synergize through distinct dendritic cell pathways to induce T cell responses: Implications for vaccines

Abstract: Toll-like receptors (TLRs) may need to cooperate with each other to be effective in detecting imminent infection and trigger immune responses. Understanding is still limited about the intracellular mechanism of this cooperation. We found that when certain TLRs are involved, dendritic cells (DCs) establish unidirectional intracellular cross-talk, in which the MyD88-independent TRIF-dependent pathway amplifies the MyD88-dependent DC function through a JNK-dependent mechanism. The amplified MyD88-dependent DC fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
145
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(160 citation statements)
references
References 49 publications
12
145
2
1
Order By: Relevance
“…Certain molecular adjuvants, such as Toll-like receptor (TLR) agonists and cytokines, can improve the quantity and quality of antigen-specific T-cell responses (6,7). Studies in mice showed that TLR2, -3, and -9 agonists activate and mature dendritic cells (DCs) to enhance immune responses (8,9) and our laboratory discovered a synergistic adjuvant effect of a combination of these agonists (9,10). We and others have also found that IL-15 is a strong cytokine adjuvant, as it promotes the homeostatic expansion of CD8 + memory T cells, and the induction of higher avidity, longer-lived T cells (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Certain molecular adjuvants, such as Toll-like receptor (TLR) agonists and cytokines, can improve the quantity and quality of antigen-specific T-cell responses (6,7). Studies in mice showed that TLR2, -3, and -9 agonists activate and mature dendritic cells (DCs) to enhance immune responses (8,9) and our laboratory discovered a synergistic adjuvant effect of a combination of these agonists (9,10). We and others have also found that IL-15 is a strong cytokine adjuvant, as it promotes the homeostatic expansion of CD8 + memory T cells, and the induction of higher avidity, longer-lived T cells (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…The up-regulation of the MyD88 gene expression correlated with the increased expression of CD11c and CD86 genes in splenic MNCs isolated from mice treated with sole Cpg ODN or tumor vaccine suggesting again that the maturation of APCs (including the DCs) was triggered after the injection of tumor vaccine (37). unlike in the splenic MNCs, a significant up-regulation of CD11c and CD86 in MNCs isolated from the bone marrow of treated mice was not detected earlier than 3 days after the first application of the vaccine or the vaccine components.…”
Section: Discussionmentioning
confidence: 95%
“…Four TLRs (TLR2-5) are expressed in both normal ovary epithelial cells and ovarian cancer cell lines (Zhou et al, 2009). The significance of the expression of multiple TLRs in a wide range of cancer cells is not fully understood; however, simultaneous activation of multiple TLR types might be able to enhance the biological response, as in the case of synergistic effects by combined TLR ligation reported for cytokine production in DCs (Whitmore et al, 2004;Roelofs et al, 2005;Warger et al, 2006;Gautier et al, 2005;Theiner et al, 2007;Zhu et al, 2008;Krummen et al, 2010) and macrophages (Sato et al, 2000;Ouyang et al, 2007). It is possible that tumor cells express multiple TLRs to recognize various DAMPs in their microenvironment, and thereby enhance the biological process triggered by TLR activation to produce favorable conditions for growth and survival.…”
Section: Positive Effects Of Tlrs In Cancer Developmentmentioning
confidence: 99%